Organizational readiness to change as a leverage point for improving safety: a national nursing home survey - Emma D. Quach; Lewis E. Kazis; Shibei Zhao; Pengsheng Ni; Valerie A. Clark; Sarah E. McDannold; Christine W. Hartmann (BMC, 2021)
Abstract Background A stronger safety climate in nursing homes may reduce avoidable adverse events. Yet efforts to strengthen safety climate may fail if nursing homes are not ready to change. To inform improvement efforts, we examined the link between organizational readiness to change and safety climate. Methods Seven safety climate domains and organizational readiness to change were measured with validated Community Living Center/CLC Employee Survey of Attitudes about Resident Safety and Organizational Readiness to Change Assessment. Safety climate domains comprised of safety priorities, supervisor commitment to safety, senior management commitment to safety, safety attitudes, environmental safety, coworker interactions around safety, and global rating of CLC. We specified models with and without readiness to change to explain CLC- and person-level variance in safety climate domains. Results One thousand three hundred ninety seven workers (frontline staff and managers) responded from 56 US Veterans Health Administration CLCs located throughout the US. Adding readiness to change reduced baseline CLC-level variance of outcomes (2.3-9.3%) by > 70% for interpersonal domains (co-workers, supervisors, and senior management). Readiness to change explained person-level variance of every safety climate domain (P < 0.05), especially for interpersonal domains. Conclusions Organizational readiness to change predicted safety climate. Safety climate initiatives that address readiness to change among frontline staff and managers may be more likely to succeed and eventually increase resident safety.